ANALISIS INOVASI MANAGERIAL KEPALAH SEKOLAH DALAM MENJAGA EKSISTENSI MIS 01 LEBONG TAMBANG - Sisvi Kartika; Jumira Warlizasusi; Aan Rifanto (Program Studi Manajemen Pendidikan Islam IAIN Bone, 2020)
A qualified madrasah is strongly influenced by the leader’s role of the Madrasah per se because managerial abilities are a significant factor in determining the success of education. One of which is by making educational innovations at the Madrasah (school) that he leads. The head of a Madrasah that has seriousness and high working performance will be capable of making good innovations. Besides, such innovations should also be espoused by reliable managerial abilities in order to capably realize an effective, conducive, and dynamic Madrasah. This study sought to find out a depiction of the managerial innovations made by the principal of MIS of Lebong Tambang in Lebong Regency, Bengkulu, in an effort to maintain the existence of Madrasah he leads. This study used a qualitative approach. The data collection techniques deployed observation, interview, and documentation techniques, and then the data were analyzed in ways according to Miles, Haberman and Saldana. This study concluded that the principal together with all teachers strived to make innovations through: preparation of school planning; development of school organization; effective involvement of teachers and staffs at school; management of facilities and infrastructure; student management; curriculum development; and management of school financial and administration.